PROBLEMS OF THE DEVELOPMENT OF THE ECOLOGICAL CULTURE OF FUTURE EDUCATORS (American Journal of Pedagogical and Educational Research, 2023)
The article identified a problem that is currently relevant, namely the concept of" environmental culture of the teacher " and the pedagogical conditions, description and methodology aimed at developing the ecological culture of future teachers of preschool educational institutions.